Determinants of outcomes following acute child encephalopathy and encephalitis: pivotal effect of early and delayed cooling. Issue 10 (16th June 2010) - Kawano, G; Iwata, O; Iwata, S; Kawano, K; Obu, K; Kuki, I; Rinka, H; Shiomi, M; Yamanouchi, H; Kakuma, T; Takashima, S; Matsuishi, T
Abstract : Background: Acute encephalopathy/encephalitis is one of the most important causatives of mortality and neurological deficit during childhood. The aim of this retrospective observational study was to investigate clinical variables and therapeutic options associated with the outcome of children with acute encephalopathy/encephalitis. Methods: Relationships between the clinical information at admission and the neurological outcome evaluated using Pediatric Cerebral Performance Category Scale (PCPC) at 12 months after admission were assessed in 43 patients who were treated at 10 Japanese paediatric intensive care units. Results: Sixteen patients were cared for at normothermia, whereas mild hypothermia was applied to 27 children. In univariate analysis, ages ≤18 months, marked elevation in serum lactate dehydrogenase (LD) and aspartate transaminase, diagnosis of either acute necrotising encephalopathy or haemorrhagic shock and encephalopathy syndrome and longer hypothermic periods were associated with increased risks of death or severe neurological deficit, whereas hypothermia showed pivotal effects: the outcome of children cooled after 12 h of diagnosis was statistically invariant with normothermic children, but was significantly worse compared with children cooled ≤12 h. In multivariate analysis, younger ages and elevated serum LD were associated with adverse outcomes, whereas early initiation of cooling was related to favourable outcomes. For normothermic children, PCPC scores were dependent on the computed tomographic findings suggestive of cerebral oedema, serum LD levels and Glasgow Coma Scale at admission. For hypothermic children, PCPC scores depended on longer delays in cooling initiation. Conclusion: Without therapeutic hypothermia, the outcome of children was determined by variables suggestive of the severity of encephalopathy/encephalitis at admission. Hypothermia may have pivotal impacts on the outcome of children according to the timing of cooling initiation following acute encephalopathy/encephalitis.